From Trash to Luxury: The Potential Role of Plant LncRNA in DNA Methylation During Abiotic Stress - Urquiaga, Maria Clara de Oliveira; Thiebaut, Flávia; Hemerly, Adriana Silva; Ferreira, Paulo Cavalcanti Gomes (Frontiers in Plant Science, 2021)
Remarkable progress has been made in elucidating important roles of plant non-coding RNAs. Among these RNAs, long noncoding RNAs (lncRNAs) have gained widespread attention, especially their role in plant environmental stress responses. LncRNAs act at different levels of gene expression regulation, and one of these mechanisms is by recruitment of DNA methyltransferases or demethylases to regulate the target gene transcription. In this mini-review, we highlight the function of lncRNAs, including their potential role in RNA-directed DNA Methylation (RdDM) silencing pathway and their potential function under abiotic stresses conditions. Moreover, we also present and discuss studies of lncRNAs in crops. Finally, we propose a path outlook for future research that may be important for plant breeding.